Architecture of modern e-learning systems - Armenski, Goce; Gushev, Marjan (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2008)
In the past two decades the area of e-learning was dominated by monolithic application silos. These e-learning platforms are usually vendor specific and do not provide the flexibility a learner needs, interoperability and pedagogical flexibility. The concept of ëwhat an application isî is rapidly changing in the recent years. With the advances of Internet technologies, as well as social interactions online, there has been a shift from monolithic application silos toward service oriented approaches where flexible granular functional components expose services accessible to applications via loosely coupled standards-based interfaces. This paper gives an overview of the existing trends in the design of modern e-learning systems emphasizing issues and challenges that will bring us to the sufficiently sophisticated eLearning system that will be able to adapt its behaviour depending on the learners knowledge, intelligently leading him to a particular goal by monitoring is progress.